The Impact of Hoax Educational Content on Instagram in Improving People’s Digital Literacy Skills - Fardiah, Dedeh; Darmawan, Ferry; Rinawati, Rini; Wira Cholifah, Yuristia; Ibrahim Abdullah, Sandi (KnE Social Sciences, 2023)
The main challenge of today’s society is the massive use of digital media, providing benefits for its users and the potential for various problems to arise. The lack of digital literacy skills in using hardware and software causes the use of digital media that is not optimal, causing violations of citizens’ digital rights. Low ethics in using digital media can create a digital space that contains much harmful content. Weak digital security has the potential to cause leakage of personal data and digital fraud. The purpose of the study was to use correlational research methods to find the educational impact of hoax content carried out by Jabarsaberhoaks through Instagram in increasing digital literacy. The study population were Instagram followers @jabarsaberhoaks, with a sample of 400 people. The results showed that the ”Jabar Saber Hoaks” strategy in monitoring the spread of fake news on social media uses active and passive monitoring. Education to the public in minimizing the space of fake news on social media was carried out using digital literacy for all components of the society. The intensity of accessibility and the technique of presenting hoax educational content on Instagram @jabarsaberhoaks has no impact on people’s digital literacy skills. Meanwhile, how hoax educational content is delivered on Instagram @jabarsaberhoaks, affects people’s digital literacy skills. Keywords: literacy, digital, hoax, hoax education